Gender Differences in ICT Competencies among Academicians at Universiti Putra Malaysia - Wong, Wong; Abdul Aziz, Sidek; Mohd Yunus, Aida Suraya; Sidek, Zakaria; Abu Bakar, Kamariah; Meseran, Hamidah; Atan, Hanafi (2005)
This paper reports on a descriptive study that was conducted to assess existing levels of information and communication technology (ICT) competencies among the academic staff of Universiti Putra Malaysia (UPM) according to gender. Specifically, it seeks to investigate if differences exist between females and males in terms of eight components (word processing, spreadsheets, databases, presentations, electronic mail, World Wide Web, multimedia and virtual class applications) related to ICT. A total of 109 academic staff participated in this study. The results of the study shows that there exists a gap between female and male academicians; in certain cases, the competencies of female academicians have even surpassed those possessed by males. The various possible reasons attributed to these results will be highlighted and discussed.